FLU-CONOMICS AND ITS IMPACT GLOBALLY WITH SPECIAL STUDY HOW TO OVERSTRIP FROM THIS GRIM FOR INDIA (IITM Journal of Business Studies, 2024)
The outbreak of coronavirus, named as COVID19  by World Health Organization (WHO) has  stunned all the nations. This has shown that the  world is not prepared for such kind of biological  threats. Every nation is trying to mitigate the  challenges posed by this disease in their capacity  but there is no ray of hope to come out from this  crisis. Lockdown and social distancing has posed  numerous challenges and affecting the various  sectors. Unemployment is at its peak within few  months since the outbreak of this pandemic. So,  this paper has tried to analyzed the economic  impact on GDP across the globe with special  reference to its effect on India. The sectors on  which it has the maximum impact and those on  which this pandemic has the least effect is also  studied. On the basis of the study undertaken  in reviving the economies from the recession of  2007-08 a concrete model has been reframed  that can help the nation in overcoming the grim  of COVID19. So this study has tried to discuss  the economic impact on the nation but also tried  to provide the solution from overcoming of this  problem that can help the countries to again  revive their economies.
Keywords: COVID19; Global; GDP; Pandemic